CRYOPRESERVATION OF SPERMATOZOA OF THREATENED ASIAN STRIPED DWARF CATFISH Mystus Vittatus (BLOCH 1794) FOR EX-SITU CONSERVATION: AN APPROACH TO PROVERY ALLEVIATION - Sarder, Md. Rafiqul Islam; Al Islam, Anas; Islam, Md. Moudud; Noor, Mirza Nusrat; Jahan, Durin Akhter (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
Cryopreservation is an important ex-situ conservation measure practiced successfully in fishes over the years. The effects of different extenders and cryoprotectants on the viability and fertilizing ability of cryopreserved sperm of Mystus vittatus were investigated in this study in order to develop a cryopreservation protocol. Milt was collected through sacrifice of males and was suspended in extender solutions. The concentration and pH of milt were found to be 7.9Ã109 - 8.1Ã109cells/ml and 8Â±0, respectively. Different concentrations of NaCl solutions (0.1% to 1.1%) were used to evaluate activation of sperm motility and it was decreased as the concentration of the NaCl solution increased. Sperm motility was completely inhibited at 1.1% and 0.8% NaCl solution with Alseverâs solution and Kurokura-2 solution respectively. Two extenders, Alseverâs and Kurokura-2 solutions and two cryoprotectants, Dimethyl sulfoxide (Me2SO) and methanol were employed to preserve the sperm. Ten percent cryoprotectants with both extenders, Alseverâs and Kurokura-2 solutions produced better motility after 5 and 10 min incubation. 15% cryoprotectant was found to be toxic to sperm. Alseverâs solution with 10% Me2SO showed better performance producing 77.5Â±1.4% and 58.8Â±1.25% equilibration and post-thaw motility than that of 73.8Â±3.15% and 52.5Â±2.5% with Kurokura-2 solution plus Me2SO respectively. Between two diluents, sperm preserved with Alseverâs solution plus Me2SO produced highest fertilization (70.0Â±7.07%) and hatching (37.5Â±13.7%), while those preserved with Kurokura-2 plus Me2SO produced 72.5Â±2.5% and 29.9Â±12.5% fertilization and hatching respectively. Fresh sperm yielded 85.0Â±0% fertilization and 48.0Â±15.5% hatching. Â The protocol developed through this study can be applied for long-term preservation of genetic materials of the threatened catfish M. vittatus and the cryopreserved sperm can be used in artificial breeding for broodstock development. Thus the protocol will help to propagate the new generation in hatcheries using cryopreserved sperm and make the fish available in captive culture systems as well as in wild which eventually helps to eradicate poverty.